2021
DOI: 10.3390/ph14060569
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens for the Management of Endometriosis: Findings and Issues

Abstract: Endometriosis, a chronic disease characterized by recurrent pelvic pain and infertility, severely impacts the health and life quality of many women worldwide. Since phytoestrogens are commonly found in a variety of foods, and estrogen is a major pathological factor for the pathogenesis of endometriosis, their possible involvement cannot be ignored. This review summarizes data on the relationship between phytoestrogen intake and endometriosis risk, and analyzes the findings from in vitro experiments, rodent end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 109 publications
0
22
0
1
Order By: Relevance
“…Clinical trials have showcased resveratrol's analgesic potential in postmenopausal women (Cooney et al, 2022), knee osteoarthritis pain (Yang et al, 2022), and endometriosis pain (Cai et al, 2021) (Table 2). Wong et al (2017) discovered that resveratrol significantly reduced pain in postmenopausal women.…”
Section: Evaluating the Efficacy Of Resveratrol In Clinical Pain Mana...mentioning
confidence: 99%
“…Clinical trials have showcased resveratrol's analgesic potential in postmenopausal women (Cooney et al, 2022), knee osteoarthritis pain (Yang et al, 2022), and endometriosis pain (Cai et al, 2021) (Table 2). Wong et al (2017) discovered that resveratrol significantly reduced pain in postmenopausal women.…”
Section: Evaluating the Efficacy Of Resveratrol In Clinical Pain Mana...mentioning
confidence: 99%
“…A study by Yu et al [129] showed that treatment with puerarin reduced the levels of estradiol and PGE2 in endometriotic rats, by inhibiting the aromatase enzyme P450 and COX-2, in addition to increasing the expression of 17β-HSD2, thus preventing the growth of endometrial tissue. Kim et al [130][131][132][133] showed that treatment with an extract obtained from flowers of P. lobata reduced the adhesion and migration of these cells, also reducing the formation of endometriotic lesions in mice. Figure 3 summarizes the main treatment options for endometriosis.…”
Section: Puerarinmentioning
confidence: 99%
“…Três revisões relataram resultados diferentes em um outro experimento similar realizado. O uso do contraceptivo associado à adição do resveratrol durante dois meses diminuiu os escores de dor e suprimiu a dismenorreia e a dor pélvica (Cai et al, 2021;Chen et al, 2019;Meresman, et al, 2021).…”
Section: O Papel Do Resveratrol No Tratamento De Endometrioseunclassified